Judiciário midiatiza(n)do: tensões entre norma e experimentação social - Mendonça, Hermundes Souza Flores de (Universidade do Vale do Rio dos Sinos, 2021)
This work is the result of a theoretical and practical reflection on the judicial realization of law in the communicational context of mediatization. We articulate the concepts of mediatization, judicialization and judicial activism to answer questions formulated in the course of the empirical study of four cases. In its empirical aspects, the thesis privileges the diversity and uniqueness of the studied cases. Theories are triggered in the service of understanding what happens in the cases, through the observation of the actions of individual and collective subjects participating in the analyzed episodes. Therefore, from a methodological point of view, we make upward and downward movements - from cases to concepts and from these to cases in which we are tentatively elaborating potentially generalizable formulations for the understanding of judicial practice in the context of mediatization. The cases show social processes mediated by judicial practice in which the activation of communicational logics brought about by mediatization generates tension in the legally standardized.
Keywords: Midiatização; Judicialização; Ativismo judicial; Mediatization; Judicialization; Judicial activism; ACCNPQ::Ciências Sociais Aplicadas::Comunicação